M-3n+5=

Simple and best practice solution for M-3n+5= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for M-3n+5= equation:


Simplifying
M + -3n + 5 = 0

Reorder the terms:
5 + M + -3n = 0

Solving
5 + M + -3n = 0

Solving for variable 'M'.

Move all terms containing M to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + M + -5 + -3n = 0 + -5

Reorder the terms:
5 + -5 + M + -3n = 0 + -5

Combine like terms: 5 + -5 = 0
0 + M + -3n = 0 + -5
M + -3n = 0 + -5

Combine like terms: 0 + -5 = -5
M + -3n = -5

Add '3n' to each side of the equation.
M + -3n + 3n = -5 + 3n

Combine like terms: -3n + 3n = 0
M + 0 = -5 + 3n
M = -5 + 3n

Simplifying
M = -5 + 3n

See similar equations:

| 9p^2(p+1)=4(p+1)-9(p+1) | | 4y+11=79 | | 4.75m+15=3m+24+m-4 | | 203.75/(-0.1)= | | .5n=3n-20 | | 5(x+9)-4=5 | | y7+6=11 | | 2x+4=2x+4.000000000000000000000000000000000000000000000000000000001 | | 4y-7=39 | | 0.5n-5=3n-25 | | 2x-5=39(7+2x) | | 2sin(x)-4-cos(x)=0 | | 6u-6=-9(u-1) | | ifBC=RLthen | | 36+12m^2+m^4=0 | | 4a*3a= | | ln(6x+2)=ln(3x-19) | | -4.3-3z-2.9-z=-3z+5.7 | | -8m-8n+p-2=-10n-9p+8 | | 12*x^2-4=0 | | t(2t+-1)=1 | | 10-(4x-1)=8-5x | | 7x+21(2x-3)=180 | | 8c*3c= | | 3x+22x-4=5(5x+6) | | (-7b+4a)+(-6a-9b)= | | 5w^2+39w+5y=0 | | 9a+19=100 | | X^2-2x+528=0 | | 98=-2(-8x+8) | | 8cos^2x-4cosx-2=0 | | 6g=6g+-34 |

Equations solver categories